Family Behavior in Maintenance Status Hb Chronic Renal Failure Patients through Family Centered Care Approach of Diet Fe Management - Hardianti, Anggia Fajar; Widyawati, Ika Yuni; Mariyanti, Herdina (Jurnal Ners, 2017)
Introduction: Erythropoietic agent as standard practice for anemia treatment, which has a function to increase the value of hemoglobin (Hb) to 12 g/dl in patients with chronic renal failure (CRF), who receiving dialysis treatment. The use of erythropoietin has to keep of the iron/Fe amount in the body. Family who have a duty of care should have knowledge, attitude, and behavior to maintain patient’s Hb by giving support to the patient to obey the Fe diet. The aimed of this study was to investigate the effect of family centered care approach in management Fe diet toward family’s behaviour in maintenance Hb level of CRF patients in hemodialysis ward, Gambiran Hospital, Kediri. Method: This study was used a pre experimental design. Total sample were 10 respondents, who met to inclusion criteria. The independent variables were knowledge, attitude, and psychomotor of family in maintenance of Hb level in CRF’s patients. The dependent variable was Fe diet management with family centered care approach. Data was collected by using a structured questionnaire and home visit observation. Result: Data was analyzed by using Wilcoxon Sign Rank Test with significance level αâ‰¤0.05. Results showed that Fe diet management with family centered care approach took effect to family’s knowledge (p=0.011), family’s attitude (p=0.005) and family’s psychomotor (p=0.005) in maintenance Hb level of CRF patients. Conclusion: Family’s knowledge, attitude, and psychomotor were effected by experiences during the care of a patient, not affordable to access information and patient’s own decision. The strengths and weaknesses in the family to got a better plan of care can be made by discuss and sharing among researcher, patient and his family. It can be concluded that Fe diet management with family centered care approach took effect to family’s behaviour. Further studies should involve larger respondents and better measurement tools to obtain more accurate results.